Association between brominated flame retardants and periodontitis: a large-scale population-based study - Jiang, Hao; Yin, Jingwen; Wang, Meixiang; Yuan, Aili; Wu, Jing; Lu, Yi (Frontiers in Public Health, 2024)
BackgroundThe association between brominated flame retardants (BFRs) and periodontitis has remained unclear.MethodsThis research included adult participants from NHANES cycles 2009–2014. Survey-weighted generalized linear regressions were used to explore the associations between BFR exposure and periodontitis. Ln-transformed BFRs were treated as quantitative variables and then divided into four quartiles for qualitative analysis. Restricted cubic splines (RCSs) were utilized to investigate potential nonlinear relationships. Quantile weighted quantile sum (WQS) regression and quantile g-computation (QGC) analysis were performed to assess the overall effect of BFRs on periodontitis.ResultsA total of 2,445 participants were included in this study. In the fully adjusted model, several ln-transformed BFR components were positively correlated with periodontitis: serum PBDE28, PBDE47, PBDE85, PBDE99, PBDE100, PBDE154, and PBB153. When expressed in quartiles, PBDE28, PBDE85, PBDE100, PBDE154, and PBB153 showed increased odds with periodontitis. We found significant nonlinear correlation between PBDE28, PBDE47, PBDE85, PBDE100, PBDE154, and PBB153 with periodontitis in the RCS regression. The WQS index for mixed BFR exposure was positively associated with periodontitis prevalence (OR: 1.52; 95% CI: 1.30–1.79, p < 0.001). Similarly, the QGC analysis showed a positive association between mixed BFR exposure and periodontitis prevalence (β: 1.29; 95% CI: 1.24–1.36, p < 0.001).ConclusionThis study indicates that overall exposure to BFRs is positively associated with the prevalence of periodontitis. Further research is needed to investigate the causal relationship and underlying mechanisms between BFRs and periodontitis.